1995
DOI: 10.1039/dt9950000783
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexes of carbohydrates: isolation and characterisation of cobalt(III) complexes containing N-substituted glycosylamine ligands derived from ethane-1,2-diamine and glucosamine

Abstract: Reaction between cis-or trans- [Co(en),CI,] + (en = ethane-I ,2-diamine) and D-glucosamine (2-amino-2-deoxy-~-glucopyranose) in neutral aqueous solution results in a very complicated product mixture including as a major component several isomeric complex ions in which the co-ordination sphere is formally made up of two ethane-I ,2-diamine units and one sugar unit. Separation of these complexes by ion-exchange chromatography, and subsequent spectroscopic and structural studies have shown that they are diastereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Subsequently, it was shown 330 that this affords four isomers with a D : L ratio of 7 : 3, which differ in the anomeric configuration of the ligand and configuration of the chelate unit (complexes like 43 with an amino group instead of a hydroxyl group). Finally, recently 331 it was shown that the composition of the product mixture is even more complicated; eight(!) isomers were isolated from the mixture and characterised by X-ray diffraction analysis.…”
Section: Complexes Of Nitrogen-containing Natural Carbohydratesmentioning
confidence: 99%
“…Subsequently, it was shown 330 that this affords four isomers with a D : L ratio of 7 : 3, which differ in the anomeric configuration of the ligand and configuration of the chelate unit (complexes like 43 with an amino group instead of a hydroxyl group). Finally, recently 331 it was shown that the composition of the product mixture is even more complicated; eight(!) isomers were isolated from the mixture and characterised by X-ray diffraction analysis.…”
Section: Complexes Of Nitrogen-containing Natural Carbohydratesmentioning
confidence: 99%
“…Corresponding complexes with chelating polyamines have been the subject of numerous subsequent studies, serving for example as model compounds for the investigation of the kinetics and mechanism of ligand exchange reactions . Co III -amine complexes with polyalcohols have been prepared as models for the elucidation of metal binding to carbohydrates . The diamagnetic Co III center is particularly suitable for this purpose, because the different species formed in solution can readily be identified by conventional NMR methods …”
Section: Introductionmentioning
confidence: 99%
“…9,102 The use of an alternative workup of the D-glucosamine (103a) ± [Co(en) 3 ] 3+ mixture (see Ref. Among the complexes isolated, 103 only compound 106 with a pyranose form of the carbohydrate ligand is a normal product. In the other complexes, D-glucosamine 103a is transformed into both D-mannosamine 103b by the Lobry de Bruyn ± van Ekenstein rearrangement, 104,105 and D-fructosylamine by the Amadori rearrangement 105 (complex 107).…”
Section: Complexes With D-metal Cationsmentioning
confidence: 99%
“…The complexes formed are diastereomerically pure and have a Dor L-configuration at the chelate point. The study 103 is undoubtedly one of the key studies in the coordination chemistry of carbohydrates, since it demonstrates extreme flexibility of unprotected monosaccharides in complexation with metals.…”
Section: Complexes With D-metal Cationsmentioning
confidence: 99%